Distal fibula fractures in professional athletes: carbon plate fixation and accelerated rehabilitation protocol can improve return to play - Marzilli, Fabio; Fidanza, Andrea; Scuccimarra, Tommaso; Mastri, Pierluigi; Viglietta, Edoardo; Erasmo, Rocco (Lo Scalpello - Journal, 2022)
Objective. The purpose of this preliminary study is to investigate whether the use of a carbon plate fixation system for distal fibula fracture, applied to an intensive rehabilitation protocol, is a good method to accelerate the return to play of professional athletes. Methods. This is a longitudinal case series with 6 months of total follow-up. Athletes of various sports, each with a minimum Tegner’s activity score of 7, who underwent fibular ORIF with carbon fiber plates in our institute for Weber B fracture were considered. The primary outcomes were: return to play (RTP) at the previous level, radiological union, and the complication rate (nonunion, hardware failure, and infection). Secondary outcomes were the AOFAS score, VAS on everyday activities and VAS after sport tested at 1, 2, 3, and 6 months. Results. Considering primary outcomes, the mean RTP measured was 75.64 days ± 10.96; for the union rate 3 patients satisfied union criteria at 1 month follow-up, 7 at 2 months, and 4 at 3 months. No complication occurred during follow-up. Conclusions. The improved elastic compatibility of the carbon plate, with respect to the bone, allows for an “extended” safety zone to accelerate the patient’s rehabilitation and return to a pre-injury athletic level.